Spin-valley-dependent transport and giant tunneling magnetoresistance in silicene with periodic electromagnetic modulations - 刘一曼;邵怀华;周光辉;朴红光;潘礼庆;刘敏 (Chinese physics B, 2017)
The transport property of electrons tunneling through arrays of magnetic and electric barriers is studied in silicene. In the tunneling transmission spectrum, the spin-valley-dependent filtered states can be achieved in an incident energy range which can be controlled by the electric gate voltage. For the parallel magnetization configuration, the transmission is asymmetric with respect to the incident angle θ, and electrons with a very large negative incident angle can always transmit in propagating modes for one of the spin-valley filtered states under a certain electromagnetic condition. But for the antiparallel configuration, the transmission is symmetric about θ and there is no such transmission channel. The difference of the transmission between the two configurations leads to a giant tunneling magnetoresistance （TMR） effect. The TMR can reach to 100% in a certain Fermi energy interval around the electrostatic potential. This energy interval can be adjusted significantly by the magnetic field and/or electric gate voltage. The results obtained may be useful for future valleytronic and spintronic applications, as well as magnetoresistance device based on silicene.